IBM Storage Solutions for SAP Applications Version 1.4 - IBM (IBM Redbooks, 2020)
This IBM® Redpaper"!publication is intended as an architecture and configuration guide to set up the IBM System Storage"!for the SAP HANA tailored data center integration (SAP HANA TDI) within a storage area network (SAN) environment. SAP HANA TDI allows the SAP customer to attach external storage to the SAP HANA server. The paper also describes the setup and configuration of SAP Landscape Management for SAP HANA systems on IBM infrastructure components: IBM Power Systems and IBM Storage based on IBM Spectrum® Virtualize. This document is written for IT technical specialists and architects with advanced skill levels on SUSE Linux Enterprise Server or Red Hat Enterprise Linux (RHEL) and IBM System Storage. This document provides the necessary information to select, verify, and connect IBM System Storage to the SAP HANA server through a Fibre Channel-based SAN. The recommendations in this Blueprint apply to single-node and scale-out configurations, and Intel and IBM Power based SAP HANA systems